Optical limiting properties of hydrophobic poly(etherimide) membranes embedded with isolated and aggregated gold nanostructures - D'Britto, Virginia; Sandeep, C. S. Suchand; Philip, R.; Bhagavatula L. V. Prasad (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2009)
A simple method to incorporate spherical or aggregated nanostructures of gold into hydrophobic poly(etherimide) membranes is demonstrated and their comparative nonlinear optical properties are investigated. When excited at 532 nm using laser pulses of 7 ns duration, a reduced transmission behaviour in both the cases, viz., polymers embedded with isolated nanoparticles and their aggregates is observed. This fits to a three-photon type nonlinear absorption process and is attributed to excited state absorption occurring in the nanostructures. Interestingly, the nonlinearity is more prominent in the aggregated nanostructures compared to the spherical nanostructures. These materials are potential candidates for optical limiting applications. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: gold nanoparticles; Nanoparticle aggregation; Nonlinear optical properties; Optical limiting; Phase transfer; Polymer nanocomposites